The community associated with the Pacific oyster (Crassostrea gigas Thunberg) in Deep Bay, Hong Kong: withspecial reference to the shell borer Aspidopholas obtecta Sowerby. - 王柏萱; Wong, Pat-shun, Patsy
published_or_final_version Zoology Master Master of Philosophy